Sifat Mekanik Baja Karbon Rendah Akibat Variasi Bentuk Kampuh Las dan Mendapat Perlakuan Panas Annealing dan Normalizing - Nukman (Jurnal Rekayasa Mesin, 2009)
Low carbon steel represent one of material which is generally used in a machine component. It has good formability and machineability, and also having the nature of able to good welding ability. Because welding can causing the happening of change metallurgi at metal, deformation and tension termal. To increase strength of extension welding that is through hot treatment by Annealing And Normalizing. The ultimated stress of specimen, highest owned by non-welding non-heat treatment (= 53,24 kgf/mm2 by e = 5,552%). The highest ultimated stress of welding specimen owned by double type V (X) weld - normalizing specimen ( = 52,85 kgf/mm2). This matter effect of level wide surface weld formed by double type V (X). The ultimate stress of nonwelding non-heat treatment specimen, highest tension is  = 11,7504 kgf/mm2. Bending test for the welding specimen, highest tension owned by spesimen Normalizing – Square type  (I) ( = 12,4032 kgf /mm2).